Liberalisme Dalam Pendidikan Islam (Implikasinya Terhadap Sistem Pembelajaran Agama Islam Di Sekolah) - Rahmat Rahmat (Prodi Manajemen Pendidikan Islam Institut Pesantren KH Chalim Mojokerto, 2018)
Humans (both teachers or learners) as the subject of education in nature is a creature who can think and be critical and able to read and change the reality of the world. Long before these teachings of Islam had earlier delivered it. The idea of liberalism (liberation) in education is the efforts to liberate human beings from the educational system is verbal, all naive, boring, and authoritarian cultures dictate and rule. Such educational practices can kill the critical and creative power of man himself. Therefore, such education should be abolished and replaced with the concept of education in accordance with the human character who has the instinct or the basis of freedom. While in Islamic education the essential concept of freedom must be in accordance with the value in the concept of Islam oriented not only to the world but also to achieve success, happiness, and prosperity in the afterlife.